The Development of Canva as an Economic Learning Media at Tholabie Islamic Boarding School Malang - Siti Kholifa Amini; Yulita Pujiharti (Economic and Education Journal (Ecoducation), 2021)
This study aims to develop Canva as a learning medium with the main subject of economics, namely consumer households for class VIII SMP. The approach used is research and development (R%D). The research method taken is Mixed methods design. The subjects in this study were students of SMP Pondok Pesantren Tholabie Malang. Data collection techniques used by researchers are observations and questionnaires. Canva is developed using the ADDIE development model that has been modified by researchers. The results showed that the Canva learning video media was feasible to be used and applied in economic learning with the subject matter of consumer households for class VIII SMP Pondok Pesantren Tholabie. The researcher uses descriptive quantitative data analysis techniques and shows the assessment of media experts (4.75) with proper and valid categories. This assessment is based on the presentation of material, language, and graphics in writing. In the assessment of material experts (5.0) with a very valid and very feasible category. This assessment is based on the presentation of the material, language, and graphics in writing the content of the material. The researcher also received a response from students of 77% which could be categorized as worthy. The results of these student responses are distributed to obtain results and measure the validity and achievement of students. In this study, researchers were only able to retrieve data online online using the google form as a data collection tool, this was due to the COVID-19 pandemic and the PPKM. The result of data analysis that has been owned by the researcher shows that the percentage level is in a feasible and valid category, this means that Canva's learning video media is effective for use in Tholabie Islamic Boarding School Junior High School.